Meningkatkan Kognitif Anak melalui Kegiatan Denah Menempel Buah di PAUD/TKQ Madani - Ardana, Sri; Wahyuni, Sri (EduInovasi: Journal of Basic Educational Studies, 2024)
This study aims to understand the outcomes of children's thinking at PAUD/TKQ Madani. The purpose of this examination is to determine if there is an improvement in children's mental capacity for learning mathematics. The examination strategy employs clear techniques. The test type is Classroom Activity Exploration. The method of information gathering uses perception and estimation, while the information collection tools use perception sheets and learning outcome tests. The exploration results show that educators and scientists collaborate in implementing learning exercises, leading to the final product examining information in cycles I and II. Among them, there is an improvement from the pre-cycle, with 6 children in the BB category (54.5%) and 5 children in the MB category (45.5%) out of 11 children, while in the main cycle, there are (82%) MB children and (18%) BSH children. Furthermore, in cycle II, there are (18%) BSH children and (82%) BSB children. The results of the review indicate an increase in the mental capacity of the younger generation at PAUD/TKQ Madani by utilizing organic products while still outlining actions.